Malaysia in transition: A comparative analysis of Asian values, Islam Hadhari and 1Malaysia - Mohd Sani, Mohd Azizuddin; Yusof, Nofhafezah; Kasim, Azahar; Omar, Rusdi (Canadian Center of Science and Education, 2009)
This paper discusses on the principles of Asian values, propagated by Malaysia fourth prime minister Mahathir Mohamad, Islam Hadhari by the fifth prime minister Abdullah Ahmad Badawi, and 1Malaysia by the current prime minister Najib Razak. This paper gives a special attention to Abdullah and Islam Hadhari because it links the Mahathir’s period to current Najib’s leadership. The intension of this paper is to prove that actually these concepts are similar in theory and practice in stressing more on Islam and neo-feudalistic Malay agenda. In fact, Islam Hadhari is ironically a concept created by Mahathir himself to counter the idea of Islamic State from the Islamic party, PAS. Therefore, even after resigning from government, Mahathir’s agenda of Asian values is still being practiced.Najib Razak, current Prime Minister, on the other hand intended to promote quality leadership performance for the public and unity among the multiracial Malaysia.Although there are differences in term of the arguments for each of the idea, it is clear that these ideas or philosophies attempt to protect the real agenda of those three leaders which were to protect the political culture of neo-feudalism and ensure the ruling United Malays National Organization (UMNO) and Barisan Nasional (BN) will stay in power.This paper shows the debates between scholars in explaining the ideas and philosophies behind those three concepts in Malaysia’s realpolitik.